1995
DOI: 10.1109/9.362875
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale smoothing error models

Abstract: A class of multiscale stochastic models based on scale-recursive dynamics on trees has recently been introduced. These models are interesting because they can be used to represent a broad class of physical phenomena and because they lead to efficient algorithms for estimation and likelihood calculation. In this paper, we provide a complete statistical characterization of the error associated with smoothed estimates of the multiscale stochastic processes described by these models. In particular, we show that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 15 publications
0
22
0
Order By: Relevance
“…Houser et al, 1998;Walker and Houser, 2001;Reichle et al, 2002a, b;Margulis et al, 2002;McLaughlin, 2002;Crow and Wood, 2003;Montaldo and Albertson, 2003;Moradkhani et al, 2005a, b;Pan and Wood, 2006;Qin et al, 2009;Montzka et al, 2011;Vrugt et al, 2013). Parada and Liang (2004) developed a new spatial data assimilation framework, an extension of the Multiscale Kalman Smoother-based (MKS-based) framework (Chou et al, 1994;Fieguth et al, 1995;Luettgen and Willsky, 1995;Kumar, 1999). This framework is innovative in the way it accounts for error propagation, dissimilar spatial resolutions, and the spatial structure within which the distribution of the data is considered.…”
Section: Optimizing Model Performance: the Potential Of Data Assimilamentioning
confidence: 99%
“…Houser et al, 1998;Walker and Houser, 2001;Reichle et al, 2002a, b;Margulis et al, 2002;McLaughlin, 2002;Crow and Wood, 2003;Montaldo and Albertson, 2003;Moradkhani et al, 2005a, b;Pan and Wood, 2006;Qin et al, 2009;Montzka et al, 2011;Vrugt et al, 2013). Parada and Liang (2004) developed a new spatial data assimilation framework, an extension of the Multiscale Kalman Smoother-based (MKS-based) framework (Chou et al, 1994;Fieguth et al, 1995;Luettgen and Willsky, 1995;Kumar, 1999). This framework is innovative in the way it accounts for error propagation, dissimilar spatial resolutions, and the spatial structure within which the distribution of the data is considered.…”
Section: Optimizing Model Performance: the Potential Of Data Assimilamentioning
confidence: 99%
“…More detailed development of these equations can be found in Chou et al (1994a) and Luettgen and Willsky (1995).…”
Section: Appendix Multiscale Smoothing Algorithmmentioning
confidence: 99%
“…A rich literature already exists for the theory, stochastic realization, and parameter estimation of multiscale models for one-dimensional processes (Basseville et al, 1992;Chou et al, 1994a;Chou, Willsky, & Nikoukhah, 1994b;Daniel & Willsky, 1997b;Fieguth & Willsky, 1996;Irving, 1998;Luettgen & Willsky, 1995) and two-dimensional systems (Chin et al, 1995;Fieguth et al, 1995Fieguth et al, , 1998Irving, Fieguth, & Willsky, 1997;Luettgen et al, 1993;Menemenlis et al, 1997). We are interested in approximating the statistics of a given "eld; that is, we intentionally sacri"ce a small amount of statistical "delity in order to obtain multiresolution models that have small state dimension d. For a surprisingly rich class of purely spatial processes, low-dimensional multiresolution models have been constructed that yield near-optimal estimation performance (that is, with statistically insigni"cant discrepancies).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, it can be derived from a more general junction-tree algorithm for general graphical Markov models (Lauritzen and Spiegelhalter 1988;Lauritzen 1992). Luettgen and Willsky (1995a) showed that the prediction errorsŷ u ¡ y u ; u 2 U , also follow a multiresolution tree-structured model. That is,…”
Section: Change-of-resolution Kalman Filtermentioning
confidence: 99%
“…In the last decade, there has been a lot of research interest in multiresolution methods, including multiresolution representations of signals based on wavelet transforms (e.g., Daubechies 1992;Mallat 1989;Meyer 1992), and multiresolution stochastic models linking coarser-scale variables to ner-scale variables in an autoregressive manner via trees (e.g., Chou et al 1994;Luettgen andWillsky 1995a, 1995b;Fieguth and Willsky 1996). An advantage of using these methods is that many signals naturally have multiscale features.…”
Section: Multiresolution Tree-structured Spatial Modelsmentioning
confidence: 99%